(3cfR GdeYGfj aj TQM MQR GdCeGfjs - (3CHhYHO Gddg eMeO Hf CMeO CMeO Hf GdMSjf GdehUdj GdMfHdj GdeYQha HTYdIs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3hHYO heeG oUfa aj GdUfGYI GdTQjaI gh GdJCdja Gdefja GdehShe HMQR GdCeGfj hhLg GdJgGfj ddTjN GdTGWHj s
(3BNQgG (B:s
(3hQRbfG TaGYJge aj jhe GdOjf hgPG BNQ eG ChQOfG ef EjVGM GdeYGfj dMQR GdCeGfj Je GdcJGH s
(3GdfSNI HgG MhGTs
(3ocJHJ GdYfGhjf hCHjGJ GdbUjOI GdeTQhMI HGdMeQIs
(3hYdjgG HYV GdJedcGJ s
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdbQGAGJ hGdJLhjOs